Plant-Soil Feedbacks Predict Native but Not Non-native Plant Community Composition: A 7-Year Common-Garden Experiment - Kulmatiski, Andrew (Frontiers in Ecology and Evolution, 2019)
Plant-soil feedbacks (PSFs) have gained attention as a potential mechanism of plant growth and coexistence, however, because they are typically measured using plant monocultures in greenhouse conditions, the link between PSFs and plant growth in field communities remains poorly tested. Here, PSFs for six native and four non-native species were measured in a seven-year, common-garden experiment. A plant community growth model was then parameterized either with PSF data (PSF model) or without PSF data (Null model). PSF and Null model predictions were compared to plant ground cover in experimental and natural communities. For eight of ten species, plant cover at the end of the experiment differed among soils cultivated by different species. For native plants, the Null model incorrectly predicted rank-order abundance for three of four experimental communities and Null model predictions were not correlated with observed plant growth. In contrast, when PSF data were added to the same model, the model correctly predicted rank-order abundance for all four experimental communities and PSF model predictions were well correlated with plant cover in experimental communities and on the landscape (R2 = 0.62). For non-native species, predictions from both models were correlated with observed species cover (R2 = 0.37 and 0.35, respectively), but there was no difference between PSF and Null model predictions. Previous studies at the study site have shown that PSF maintains alternate-state native and non-native plant communities. Here it was shown that PSF is also critical for determining species composition within native plant communities, but that other mechanisms appear to be necessary to simulate the rapidly-fluctuating abundances of the short-lived, non-native species in this system. Using a relatively long-term field experiment, this study provided unusually direct evidence for the role of PSF in determining plant abundance in plant communities in field conditions, at least for long-lived native plants.